Brand as a strategic asset of transnational companies: essence, elements and management (Economics and region, 2025)
The role of the brand as a strategic asset of international organizations is analyzed through the consideration of the works of shoolars and international financial reporting standard. The essence of the concepts of brand and branding in contemporary global markets is revealed, and the role of the brand relative to other assets in the portfolio of international companies is defined. A definition of brand and branding is proposed, along with a characterization of derivative brand elements such as name, logo, symbol, slogan, visual talent and packaging that directly influence its value within the portfolio of intangible assets. Brand has been defined as a complex socio-cultural and communicative formation that represents a set of associations, emotional reactions, values, and visual-symbolic characteristics that are formed in the consumer's mind as a result of interaction with a product, service, or organization and ensure its differentiation in the market. Having studied the available sources, it was concluded that branding should be defined as a set of strategic actions aimed at forming, developing and supporting a brand in order to ensure its stable market position. Branding plays the role of simplifying the choice for the consumer, forming emotional and functional associations, which contributes to increasing loyalty and consumer self-esteem. The article emphasizes the growing importance of intangible assets in global markets, which directly affects the value of brands as one of the key assets, particularly from the perspective of investment focus aimed at their development. A trend is identified toward the increasing share of brands as intangible assets among international companies that are sectoral leaders and owners of the highest-capitalized brands. The practical value of this study lies in its ability to demonstrate the extent to which the brand, as an intangible asset, influences the competitiveness and market capitalization of international companies, as well as asset management strategy itself. Future research should focus on improvement of brand valuation methods and harmonizing financial reporting standards, which is critically important in the process of determining the real value of a brand in a company's asset portfolio.
Keywords: brand; branding; intangible assets of company; international brand; international company; intangible asset management